Impact of Salmonella Control Programmes in Poultry on Human Salmonellosis Burden in Greece - Myrsini Tzani; Georgia Mandilara; Joana Gomes Dias; Theologia Sideroglou; Anthi Chrysostomou; Kassiani Mellou (MDPI AG, 2021)
Since 2008, veterinary authorities in Greece have implemented national control programmes (NSCPs) targeting S. Enteritidis (SE) and S. Typhimurium (ST) in poultry. We assessed the effect of the programs on the reported number of human isolates. Using monthly data for 2006-2017, we defined two groups (SE, ST) and one control group with serotypes unrelated to poultry or eggs. For SE we also analysed data for 2006-2015 due to a multi-county SE outbreak in 2016. We performed an interrupted time series analysis and used a negative binominal regression model. For both SE and ST, there was no significant trend of the isolation rate before or after NSCPs' introduction. After the NSCPs' introduction there was an increasing rate (IRR: 1.005, 95% CI: 1.001-1.008) for control serotypes and a decreasing one for SE (IRR: 0.990, 95% CI: 0.986-0.995) (for 2009 to 2015 analysis). From 2006 to 2017, NSCPs had a statistically significant impact on the number of SE isolates that decreased by 49% (IRR:0.511, 95% CI: 0.353-0.739). No impact was shown on the number of ST (p-value = 0.741) and control isolates (p = 0.069). As a conclusion, NSCP's implementation was associated with decreased SE isolates and overall burden of salmonellosis; however further measures aiming at human salmonellosis due to ST, should be considered.